Loyalitas Konsumen E-Commerce Shopee Berbasis Pengalaman Belanja Online - Nur Hikmah; Sofia Ulfah (Jurnal Manajemen Bisnis Era Digital, 2024)
This study aims to determine the effect of online shopping experience on consumer loyalty in Shopee e-commerce. This type of research uses quantitative research and variable measurement is carried out using a Likert scale. The sample in this study uses a questionnaire method. The population in this study are consumers who use and shop on the Shopee application. The sample taken in this study was 100 respondents. The analysis methods used in this study are validity tests, reliability tests, simple linear regression tests, partial tests (T tests), and determinant coefficient tests (R2). Based on what the researchers have tested, the results of this study indicate that online shopping experience has a positive and significant effect on consumer loyalty. The better the online shopping experience felt by consumers, the more it can increase consumer loyalty.